Assessment of nursing students' self-esteem at a university in the South of Minas Gerais (Brazil) - Erika Cássia Lopes Chaves; Talita Prado Simão; Iara Siqueira de Oliveira; Isis Prado de Souza; Denise Hollanda Iunes; Denismar Alves Nogueira (Universidad de Antioquia, 2013)
Objective. To assess the self-esteem of nursing students and explore its relationship with professional training factors that could affect it. Methodology. Descriptive research, involving 135 nursing students at a university in the South of the state of Minas Gerais (Brazil). Data collection was performed between May and September 2011, using a self-report form that collected information about the sociodemographic characteristics and satisfaction with the career chosen, as well as the Rosenberg Self-Esteem Scale. Results. From the total, 90% of students were female, 41% were 20 years of age or younger, and 96% were single. One in each three was taking the first year of their program. Concerning the self-esteem level, 68% presented high self-esteem, 30% average and 2% low. A positive relationship was found between the level of self-esteem and professional perspective (p=0.011). Conclusion. Most nursing students presented high self-esteem, which was related to the professional perspective.